2018
DOI: 10.3390/ijms19102967
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis of Lettuce (Lactuca sativa L.) Reveals Molecular Basis-Associated Auxin and Photosynthesis with Bolting Induced by High Temperature

Abstract: Bolting is a key process in the growth and development of lettuce (Lactuca sativa L.). A high temperature can induce early bolting, which decreases both the quality and production of lettuce. However, knowledge of underlying lettuce bolting is still lacking. To better understand the molecular basis of bolting, a comparative proteomics analysis was conducted on lettuce stems, during the bolting period induced by a high temperature (33 °C) and a control temperature (20 °C) using iTRAQ-based proteomics, phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 59 publications
6
25
1
Order By: Relevance
“…On day 8, the growing point became larger and less prominent, showing ower bud differentiation starting (Fig. 1C), which is consistent with our previous research results [26].…”
Section: Effect Of High Temperature On Bolting Of Lettucesupporting
confidence: 93%
See 1 more Smart Citation
“…On day 8, the growing point became larger and less prominent, showing ower bud differentiation starting (Fig. 1C), which is consistent with our previous research results [26].…”
Section: Effect Of High Temperature On Bolting Of Lettucesupporting
confidence: 93%
“…The researchers found that trehalose can enhance the tolerance of saccharomyces cerevisiae cells to heat [37][38]. Our previous studies also showed that high temperature induced bolting of lettuce was achieved by increasing photosynthesis, carbohydrate metabolism, etc [26]. It was found in this study that the content of fructose and sucrose reached the maximum value on the 4th day after high temperature treatment (Fig.…”
Section: Fructose May Participate In Early Bolting Induced By High Tesupporting
confidence: 51%
“…Inomata et al [11] suggested that their results provide additional insights into carbohydrate metabolism regulation under ambient and adverse conditions. Hao et al [12] indicated that a high temperature enhances the function of photosynthesis and auxin biosynthesis to promote the process of bolting, which is in line with the physiology and transcription levels of auxin metabolism. Furthermore, drought stress [13] and ultraviolet-B stress [14] were also used for mechanism analyses in maize and Clematis terniflora DC, respectively.…”
mentioning
confidence: 96%
“…Gao et al [10] indicated that photosynthesis suppression, cytoskeleton and cell wall adjustment, lipid metabolism/transport, reactive oxygen species scavenging, and carbohydrate metabolism were closely associated with the cold stress response. On the other hand, Inomata et al [11] and Hao et al [12] performed proteomics to identify the mechanisms in rice and lettuce, respectively, under high temperature. Inomata et al [11] suggested that their results provide additional insights into carbohydrate metabolism regulation under ambient and adverse conditions.…”
mentioning
confidence: 99%
“…Therefore, lettuce yield may be negatively affected by less marketable heads, the presence of bolted plants, and the appearance of disorders such as tipburn (Jenni et al, 2013). Bolting is a process in which the lettuce stem elongates after the transition from vegetative to reproductive stage that negatively affects lettuce marketability and is strongly influenced by environmental factors, such as temperature and photoperiod, as well as genetic variation (Hao et al, 2018). Tipburn is a physiological disorder commonly associated with localized calcium deficiency and leaf margin necrosis that occur in newly formed leaves and is exacerbated by warm temperatures and high relative humidity that inhibits calcium translocation from evapotranspiration (Barta and Tibbits, 2000; Jenni et al, 2013).…”
mentioning
confidence: 99%